GE_GERICHTE P/19854/2022 vom 19. Februar 2025 - GE Cour de justice (2025)
PORNOGRAPHIE DURE;EXAMEN PSYCHIATRIQUE;IN DUBIO PRO REO;ERREUR DE DROIT(DROIT PÉNAL);RESPONSABILITÉ(DROIT PÉNAL) | CP.197.al4; CP.197.al5; CP.197.al6; CP.21; CPP.389; CPP.139.al2; CP.20; CP.19; CP.69